Tipologi Kesalahan Praktik Wudhu Siswa Menengah dalam Perspektif Fikih Ibadah - Zaid Muzaqi; Ubaidillah Ubaidillah (MAN 4 Kota Pekanbaru, 2026)
This study aims to identify and analyze errors in ablution (wudhu) practices among middle-level Islamic students and to examine the factors contributing to these errors from the perspective of Islamic jurisprudence. A qualitative descriptive case study design was used, with data collected through structured observations and semi-structured interviews based on the obligatory and recommended elements of ablution described in classical and contemporary fiqh literature. The findings show that most errors occurred in obligatory parts of ablution, especially incomplete washing of the elbows and insufficient wiping of the head. Students also frequently neglected recommended practices, such as inhaling water into the nose. These errors were mainly influenced by incorrect habits formed at an early age and limited individual supervision during practical learning. The study indicates that mistakes in obligatory elements may affect the validity of ritual worship. Therefore, learning of Islamic jurisprudence should place greater emphasis on practice-based instruction supported by closer supervision during ritual training.